When Forms Come Alive : Sixty Years of Restless Sculpture. - Stewart, Neil; Rugoff, Ralph; Rudd, Natalie (London : Hayward Gallery Publishing, 2024)
Asawa, Ruth ; Baghramian, Nairy ; Barlow, Phyllida ; Benglis, Lynda ; Blazy, Michel ; Bosquê, Paloma ; Brzeski, Olaf ; Jeong Hwa, Choi ; Donovan, Tara ; DRIFT ; Fàbregas, Eva ; Hendry, Holly ; EJ Hill ; Humeau, Marguerite ; Moulène, Jean-Luc ; Nengudi, Senga ; Neto, Ernesto ; Puryear, Martin ; Ronay, Matthew ; Solar Abboud, Teresa ; West, Franz
When Forms Come Alive: Sixty Years of Restless Sculpture, Hayward Gallery, London, 7 February - 6 May 2024
boek